Education and risk of incident dementia during the premotor and motor phases of essential tremor (NEDICES). Issue 33 (August 2016) - Benito-León, Julián; Contador, Israel; Louis, Elan D.; Cosentino, Stephanie; Bermejo-Pareja, Félix
Abstract : Abstract: Individuals with late-onset essential tremor (ET) (e.g., older adults) seem to have an increased prevalence of mild cognitive impairment and dementia, and a higher risk of incident dementia. It is well-known that education has a protective role against dementia in individuals without a pre-existing neurologic disorder, but evidence regarding the maintenance of this effect during the premotor and motor phases of ET is unknown. Our aim was to determine the influence of education on the risk of dementia in a population-based cohort of ET patients and controls. In a prospective study (Neurological Disorders in Central Spain), participants ≥65 years old were evaluated twice: at baseline (1994–1995) and at follow-up (1997–1998). There were 3 groups: premotor (i.e., participants first diagnosed with incident ET at follow-up), prevalent ET (i.e., participants diagnosed with ET at baseline and at follow-up), and controls. Participants were stratified into lower education (≤primary studies) versus higher education (≥secondary studies) categories. Dementia risk was estimated using Cox proportional-hazards models (higher education control group = reference category). Among the participants, 3878 had a mean duration of follow-up of 3.2 years. Eight (16.7%) of 48 lower education premotor ET patients developed incident dementia versus 1 (3.3%) of 30 higher education premotor ET patients, 9 (7.1%) of 126 lower education prevalent ET patients, 7 (8.8%) of 80 higher education prevalent ET patients, and 92 (4.9%) of 1892 lower education controls ( P < 0.001). In comparison to the higher education controls, the adjusted hazard ratios for incident dementia were 5.84 (lower education premotor ET, P < 0.001); 1.36 (higher education premotor ET, P = 0.76); 2.13 (lower education prevalent ET, P = 0.04); 2.79 (higher education prevalent ET, P = 0.01); and 1.66 (lower education controls, P = 0.01). Our results suggest that a higher educational attainment may ameliorate the risk of incident dementia during the premotor phase of ET, but not in the motor phase.